Humoral Immune Responses to a Single Allele PfAMA1 Vaccine in Healthy Malaria-Naïve Adults - Remarque, Edmond J.; Roestenberg, Meta; Younis, Sumera; Walraven, Vanessa; van der Werff, Nicole; Faber, Bart W.; Leroy, Odile; Sauerwein, Robert; Kocken, Clemens H. M.; Thomas, Alan W. (PLOS ONE, 2012)
Plasmodium falciparum apical membrane antigen 1 (AMA1) is a candidate malaria vaccine antigen expressed on merozoites and sporozoites. The polymorphic nature of AMA1 may compromise vaccine induced protection. The humoral response induced by two dosages (10 and 50 µg) of a single allele AMA1 antigen (FVO) formulated with Alhydrogel, Montanide ISA 720 or AS02 was investigated in 47 malaria-naïve adult volunteers. Volunteers were vaccinated 3 times at 4 weekly intervals and serum samples obtained four weeks after the third immunization were analysed for (i) Antibody responses to various allelic variants, (ii) Domain specificity, (iii) Avidity, (iv) IgG subclass levels, by ELISA and (v) functionality of antibody responses by Growth Inhibition Assay (GIA). About half of the antibodies induced by vaccination cross reacted with heterologous AMA1 alleles. The choice of adjuvant determined the magnitude of the antibody response, but had only a marginal influence on specificity, avidity, domain recognition or subclass responses. The highest antibody responses were observed for AMA1 formulated with AS02. The Growth Inhibition Assay activity of the antibodies was proportional to the amount of antigen specific IgG and the functional capacity of the antibodies was similar for heterologous AMA1-expressing laboratory strains. Trial Registration ClinicalTrials.gov NCT00730782